2016
DOI: 10.2139/ssrn.2812591
|View full text |Cite
|
Sign up to set email alerts
|

Mafia, Elections and Violence against Politicians

Abstract: Organized crime uses political violence to influence politics in a wide set of countries. This paper exploits a novel dataset of attacks directed towards Italian local politicians to study how (and why) criminal organizations use violence against them. We test two competing theories to predict the use of violence i) before elections, to affect the electoral outcome and ii) after elections, to influence politicians from the beginning of their term. We provide causal evidence in favor of the latter hypothesis. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 27 publications
4
22
0
Order By: Relevance
“…Evidence from Italy indicates that violence is most likely to occur after elections to influence policy, rather than being committed before elections to affect electoral outcomes. It is usually directed at local politicians and most often takes the form of arson and threatening letters (Daniele and Dipoppa 2017). Its aim is generally to provoke their removal or render them less effective in pursuing agendas that the group dislikes (Dal Bó, Dal Bó, and Di Tella 2003).…”
Section: Violence Against Politiciansmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence from Italy indicates that violence is most likely to occur after elections to influence policy, rather than being committed before elections to affect electoral outcomes. It is usually directed at local politicians and most often takes the form of arson and threatening letters (Daniele and Dipoppa 2017). Its aim is generally to provoke their removal or render them less effective in pursuing agendas that the group dislikes (Dal Bó, Dal Bó, and Di Tella 2003).…”
Section: Violence Against Politiciansmentioning
confidence: 99%
“…Gender features in only a marginal way in these literatures, despite observations in passing that the majority of perpetrators are male (James et al 2016) and that murdered politicians also tend to be male (Daniele 2017). Yet incorporating a gender lens into the study of violence against politicians does more than just highlight the gendered identities of victims and perpetrators.…”
Section: Violence Against Politiciansmentioning
confidence: 99%
“…This literature examines the impact of organized crime on democratic governance, which is fulfilled by the manipulation of the electoral outcomes (Acemoglu et al 2013;Daniele and Geys 2015). Along this line, Daniele and Dipoppa (2017) analyzed how organized crime manipulates electoral outcomes using violence. Moreover, De Feo and De Luca (2017) showed that mafia obtained economic advantages in exchange for its electoral support while Di Cataldo and Mastrorocco (2020) revealed that local governments infiltrated by criminal organization spent more for the construction sector and waste management than in other areas of public utility.…”
Section: Introductionmentioning
confidence: 99%
“…The expansion of Cosa Nostra in Sicily was contemporaneous with the birth of similar 6 The effect of mafia presence is the topic of several empirical studies. Mafia expansion and presence is found to deteriorate political competition and to affect electoral outcomes [Daniele and Geys, 2015, Daniele and Dipoppa, 2017, De Feo and De Luca, 2017, Alesina et al, 2018, Acemoglu et al, 2020, Di Cataldo and Mastrorocco, 2019. Mafia presence also generates sizable losses in terms of economic resources such as local GDP or productivity [Peri, 2004, Albanese and Marinelli, 2013, Pinotti, 2015.…”
Section: Organized Crime In Italymentioning
confidence: 99%